VALUE ADDED TAX ACCOUNTING ON ONLINE TRANSACTIONS IN MARKETPLACE DURING THE COVID-19 PANDEMIC TIME - Ardillah, Kenny (2021)
The level of tax supervision on online sales has still amounted to a very minimal level by the Directorate of General of Taxes with the potential for taxes on online transactions that the number continues to increase from year to year. The purpose of this research is to analyze the application of Value Added Tax accounting calculations and records for online transactions through the marketplace under Law Number. 42 of 2009 and the applicable Statement of Financial Accounting Standards. This type of research used in this research is qualitative research with a descriptive approach. This research was conducted at CV. ABC, which is a small-scale company in the field of online retail sales with a business domiciled in Tangerang Regency. The data collection technique in this research is direct observation by conducting data collection and interviews with parties authorized by the company. The application of Value Added Tax accounting at CV. ABC is under Law No. 42 of 2009 and Statement of Financial Accounting Standards No. 14 Revision 2014. The method used by the company to record Value Added Tax is the accrual basis method and the basis for the imposition of Value Added Tax on CV. ABC is the selling price. The value-added tax rate applied by the company is 10% of the selling price of inventory by recording inventory using a perpetual method and inventory counting using the FIFO method. This study has limited research subjects, namely one company that represents a retail company in Tangerang. It is hoped that the application of Value Added Tax accounting can be applied to all business sectors, both small, medium, and large in a computerized accounting information system that can support the contribution of depositing and reporting Value Added Tax input and output for every online transaction.